Pengaruh Kesadaran Lingkungan dan Pemasaran Hijau terhadap Keputusan Pembelian Tumbler pada Mahasiswa Kewirausahaan Universitas ST Bhinneka - Anastasya Nabila br Tarigan; Zhafirah Alaina; Rizki Ananda; Fauziah Annisa; Widya Yolanda Br Siregar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The increasing environmental damage caused by the accumulation of plastic waste has encouraged the urgency of sustainable consumption behavior. This study aims to analyze the influence of environmental awareness and green marketing on tumbler purchasing decisions among Entrepreneurship students at Satya Terra Bhinneka University. The method used is quantitative with a non-experimental correlational design. Data were collectted through purposive sampling technique with a Likert scale questionnaire instrument. Data analysis used SPSS which includes validity, reliability, classical assumptions, multiple linear regression, F test, and T test. The results of the study indicate that partially, green marketing has a significant positive influence on tumbler purchasing decisions. Meanwhile, environmental awareness does not show a significant influence, which indicates that personal environmental concern has not been a major factor for students in purchasing tumblers. The determination value of 0,461 indicates that the two independent variables contribute 46,1% to the variation in purchasing decisions. This study concludes the importance of an effective green marketing strategy for institutions and business actors to promote sustanaible products.